Giant appendicolith mimicking as foreign body: A case report - Hemangi R. Athawale; Natasha Vageriya; Nitin P. Dhende; Sachin Patil; Hussain Kotawala (Elsevier, 2016)
Acute appendicitis is one of the most common surgical emergencies. However, atypical clinical presentation and imaging can cause diagnostic confusion. We report a case of a 3 yr old girl with doubtful history of foreign body ingestion and presenting to us with features of sub acute intestinal obstruction. Serial Computerized Tomography scans (CT) were suggestive of single foreign body (FB) in distal illeum with high attenuation. But the nature of FB could not be determined on history or imaging. However on exploration there was acute appendicitis with a giant appendicolith at the base of the appendix. Appendectomy with retrieval of the appendicolith was done. Post operatively patient had complete relief of symptoms.